2005
DOI: 10.1038/sj.eye.6701820
|View full text |Cite
|
Sign up to set email alerts
|

Effect of illumination on visual function after monofocal and multifocal intraocular lens implantation

Abstract: Purpose To compare best-corrected visual acuity (BCVA) and contrast sensitivity (CS) under different levels of illumination in patients who had monofocal and multifocal intraocular lenses (IOLs) and to establish the effect of different lighting conditions on vision in the two groups of patients. Methods We retrospectively reviewed 27 patients who underwent phacoemulsification for age-related cataract and IOL implantation of either monofocal (SI30NB; n ¼ 10, 37%) or multifocal (SA40N; n ¼ 17, 63%) IOLs. Binocul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Studies of more recent lenses including the Acri.LISA 366D (60), ReSTOR, ReZoom (61, 62), and Tecnis (31, 60, 61, 63) also demonstrated that monofocal controls offered the best performance particularly under adverse conditions such as at lower contrast levels or under glare conditions (32, 33, 64) or lower spatial frequency (65), under photopic but not mesopic conditions (66), or under monocular but not binocular conditions (67). Only a few studies did not find any significant differences in contrast sensitivity between monofocal and multifocal Array (68), ReSTOR (32, 69–707172), Tecnis (73), or Lentis M-Plus lenses (60). One study of the Tecnis Symfony reported no differences in contrast sensitivity between the Symfony and the monofocal control at any spatial frequency (38).…”
Section: Resultsmentioning
confidence: 99%
“…Studies of more recent lenses including the Acri.LISA 366D (60), ReSTOR, ReZoom (61, 62), and Tecnis (31, 60, 61, 63) also demonstrated that monofocal controls offered the best performance particularly under adverse conditions such as at lower contrast levels or under glare conditions (32, 33, 64) or lower spatial frequency (65), under photopic but not mesopic conditions (66), or under monocular but not binocular conditions (67). Only a few studies did not find any significant differences in contrast sensitivity between monofocal and multifocal Array (68), ReSTOR (32, 69–707172), Tecnis (73), or Lentis M-Plus lenses (60). One study of the Tecnis Symfony reported no differences in contrast sensitivity between the Symfony and the monofocal control at any spatial frequency (38).…”
Section: Resultsmentioning
confidence: 99%
“…15 Maintaining contrast sensitivity is important because it is a determinant of near-vision performance. Figure 1 shows the near and distance uncorrected visual acuities in all 52 eyes in our study.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest no difference in glare disability induced by halogen light similar to oncoming vehicle headlights for patients implanted with monofocal and multifocal IOLs. Elgohary and Beckingsale [27 ] compared best-corrected visual acuity (BCVA) and contrast sensitivity under different levels of illumination in patients who had monofocal IOLs (AMO S1 40 NB) and MFIOLs (Array IOL SA 40 N) to establish the effect of different lighting conditions on vision in the two groups of patients. They concluded that distance and near BCVA and contrast sensitivity improve with increasing illumination in patients with monofocal and multifocal IOLs, but remain comparable in the two groups under common levels of indoor illumination.…”
Section: Contrast Sensitivity and Multifocal Intraocular Lensmentioning
confidence: 99%